Comparative Study on Sealing Performance of 2D and 3D Models for Pressurized Cable Crown Sheave - Wu, Zebing; Zhu, Xiaochun; Liu, Kenan; Zhang, Zihao; Lin, Yifei (Scientific Journal of Technology, 2026)
To address the seal failure and leakage problems of the pressurized cable crown sheave operating under high-pressure conditions of 35–50 MPa, 2D and 3D solid finite element models (FEMs) for the main sealing structure were established to investigate the sealing performance of the O-ring seal.As the fluid pressure increased to 50 MPa, the von Mises equivalent stress of the O-ring reached 16.588 MPa, which is close to the allowable stress limit of the material. Beyond this pressure threshold, the region with the maximum equivalent stress is prone to tearing, leading to seal failure.Three-dimensional FEM analysis was conducted to characterize the deformation, equivalent stress and contact pressure behaviors of the O-ring. The results show that the mechanical response of the O-ring is consistent with the predictions of the 2D axial propulsion model, which verifies the effectiveness of the 2D model under symmetric loading conditions.However, for scenarios involving O-ring twisting or asymmetric loading, 3D FEM analysis is indispensable to obtain accurate simulation results.This study provides a valuable reference for the sealing design of similar sealing structures in engineering applications.